Occurrence of Endoparasites in Adult Swedish Dogs: A Coprological Investigation - Grandi, Giulio; Victorsson, Ida; Osterman-Lind, Eva; Höglund, Johan (Frontiers in Veterinary Science, 2021)
The occurrence of endoparasites in Swedish adult dogs (n = 303) was investigated between January and October 2014. Included dogs had to be clinically healthy, older than 1 year and untreated with anthelmintics or endectocides for at least 3 months prior to sampling. They were grouped according to age, category of dog and time since last antiparasitic treatment. Samples were analyzed by flotation to detect parasitic eggs and cysts/oocysts. Among these, 129 (43%) dogs were also analyzed with the Baermann-technique to detect cardiopulmonary larval stages. Parasite dispersal stages were found in 24 (7.9%, CI 95% 4.9–10.1) of the dogs at flotation, while no dog shed cardiopulmonary larval stages. Giardia sp. cysts were observed in 2.6% (n = 8) of dogs examined, cysts of Sarcocystis spp. were observed in 0.6% (n = 2), oocysts of Cystosisopora ohioensis were found in one dog (0.3%). Eggs of Toxocara canis (2.3%, n = 7), Uncinaria stenocephala (1.3%, n = 4) and Trichuris vulpis (0.3%, one dog) were found. None of the dogs were diagnosed with more than one species. Although the occurrence of endoparasites was above the average in dogs ≤ 2 years of age (11.5%), nematodes were more common in older dogs ≥4 years (77.0%). Although the occurrence was lower in working/exhibition dogs (5.9%) than in companion dogs (8.4%) and hunting-dogs (8.6%), these differences were not significant. However, dogs exposed to prey according to the owner had a statistically significant higher prevalence than other dogs (20.5 vs. 5.7%). The Odds Ratio (OR) was 4.0 (CI 95%, 1.58–10.11) for dogs having access to prey, 2.4 (CI 95%, 0.37–8.06) for dogs staying at day-care, and 2 (CI 95%, 0.96–5.96) for bitches. Furthermore, a significant association was observed between infection with nematodes and exposures to prey (p = 0.006). As a reference, data on the endoparasites in canine fecal samples submitted to the National Veterinary Institute (SVA, Uppsala) during 2014 are presented. Overall, this study shows a low occurrence of endoparasites among dogs in Sweden. Any risk-assessment on zoonotic parasites as well as deworming recommendations will take advantage from these updated figures.